The Use Of Learning Technology In Elementary School - Fitriyati, Fina; Dwi Utari, Mutia; Maulida Astuti, Utami; Rachmawati, Umi (Prosiding University Research Colloquium, 2021)
In the advance of the times in the era of revolution in the 4.0 era was one of the greatest challenges facing teachers in Indonesia. Because the quality of education has become a refusal to measure the success of the younger generation in the face of the era of revolution 4.0. A teacher in this age must embrace technology, for a teacher who is devoid or less of knowledge of technology cannot instil in his students the critical power to become a revolutionary human being. This paper discusses the literature of technology utilization in education. The teacher and the pupil have the ability and knowledge in the field of information technology. The various technological tools teachers use in school visits among others, LCDs, laptops, computers and so on. To be a teacher with knowledge of technology must also be supported by the government through training, socialization, seminars.